Nurses' Knowledge and Teaching of Possible Postpartum Complications. Issue 6 (November 2017) - Suplee, Patricia D.; Bingham, Debra; Kleppel, Lisa
Abstract: Purpose: The purpose of this study was to assess postpartum nurses' knowledge of maternal morbidity and mortality, and information they shared with women before discharge about identifying potential warning signs of postpartum complications. Study Design & Methods: Registered nurses (RNs) who care for women during postpartum ( N = 372) completed an electronic survey. Descriptive statistics and bivariate analyses were used for data analysis. Results: Fifty-four percent of nurse participants were aware of the rising rates of maternal mortality in the United States and 12% accurately reported the correct percentage of deaths that occurred during the postpartum period. Ninety-three percent of nurses were more likely to identify hemorrhage as a leading cause of maternal mortality. On the day of discharge, 67% of RNs spent less than 10 minutes focusing on potential warning signs. Ninety-five percent of RNs reported a correlation between postpartum education and mortality; however, only 72% strongly agreed it was their responsibility to provide this education. Nurse respondents who were over the age of 40 were significantly more likely to report feeling very competent when providing education on all of the postpartum complication variables measured ( p values <0.001-0.003). Clinical Implications: The majority of nurses in this study were not up-to-date on the rates and timing of maternal mortality during the postpartum period in the United States. They did not always provide comprehensive education to all women prior to discharge from the hospital after childbirth. There is a need for nurses to provide consistent messages about potential warning signs that may ultimately reduce maternal death and severity of maternal complications. Abstract : In this study, registered nurses who care for women during postpartum were surveyed to assess their knowledge of maternal morbidity and mortality, and the information they share with women before discharge from the hospital about potential warning signs of postpartum complications. Findings suggest postpartum nurses need an update on these topics so they can offer women accurate information before their hospital discharge after childbirth that is vital to their wellbeing during the postpartum period.